Richness and large-scale distribution of marine benthic caridean shrimps (Decapoda: Caridea) from the Eastern Tropical Pacific - Martínez-Guerrero,Betel (2018)
Abstract Based on an updated checklist of the benthic caridean shrimp fauna of the Eastern Tropical Pacific (ETP), we analyzed their large-scale species richness distribution patterns using a grid approximation. Caridean fauna is composed of 183 species belonging to 67 genera and 18 families. Alpheidae, Palaemonidae and Thoridae contributed largely to species richness. Alpheus and Synalpheus were the most diverse genera. Most species (24%) have a narrow distribution inhabiting a single grid, and as many as 135 are restricted to < 5 grids. Mexico has the largest richness (130) besides Ecuador (98) and Panama (75). Richness among grids varies largely; overall, it is larger around Galapagos and Panama, Colombia, Costa Rica and the Gulf of California. There was a meaningful correlation between a proxy of sampling intensity and richness, suggesting that along with habitat heterogeneity or large-scale evolutionary processes currently invoked as richness drivers, the pattern can also be related to differences in research efforts. Exponential fitting and Chao2 index suggest that the caridean faunal inventory from the ETP is still far from being complete. Overall, the results call for a more thoughtful and systematic sampling scheme in order to get information from poorly sampled environments and areas in the ETP.